Geographic Information Systems: Tools for Displaying In-Library Use Data - Mandel, Lauren H. (Information Technology and Libraries, 2010)
In-library use data is crucial for modern libraries to understand the full spectrum of patron use, including patron self-service activities, circulation, and reference statistics. Rather than using tables and charts to display use data, a geographic information system (GIS) facilitates a more visually appealing graphical display of the data in the form of a map. GISs have been used by library and information science (LIS) researchers and practitioners to create maps that display analyses of service area populations and demographics, facilities space management issues, spatial distribution of in-library use of materials, planned branch consolidations, and so on. The “seating sweeps” method allows researchers and librarians to collect in-library use data regarding where patrons are locating themselves within the library and what they are doing at those locations, such as sitting and reading, studying in a group, or socializing. This paper proposes a GIS as a tool to visually display in-library use data collected via “seating sweeps” of a library. By using a GIS to store, manage, and display the data, researchers and librarians can create visually appealing maps that show areas of heavy use and evidence of the use and value of the library for a community. Example maps are included to facilitate the reader’s understanding of the possibilities afforded by using GISs in LIS research.